2018
DOI: 10.14434/iujur.v4i1.24491
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Gut Microbiome

Abstract: The gut microbiome has received increasing interest in past years due to its link to many diseases and its potential in therapy. One often-overlooked and newer area of research is the sexual dimorphism in the gut microbiome, and how it relates to the sex differences in behavior, diseases, and the underlying makeup between that of males and females. Reviewing the literature has demonstrated that in several organisms, adult males and females do naturally have different compositions of gut microbes. Differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This failure is probably a reflection of the multifactorial and heterogeneous nature of this disease, as well as the lack of tools for its accurate diagnosis and for quantitative disease staging 30,31 . In addition, sex is rarely considered as a biological variable in these numerous and interesting studies, despite the reported sexual dimorphism of the gut microbiota 32 , the innate immune system 33 and the liver itself. As a result, in-depth studies conducted in relevant models are necessary to fully understand the natural history of NAFLD, and to identify sex-dependent determinants of NAFLD progression.…”
Section: [H1] Introductionmentioning
confidence: 99%
“…This failure is probably a reflection of the multifactorial and heterogeneous nature of this disease, as well as the lack of tools for its accurate diagnosis and for quantitative disease staging 30,31 . In addition, sex is rarely considered as a biological variable in these numerous and interesting studies, despite the reported sexual dimorphism of the gut microbiota 32 , the innate immune system 33 and the liver itself. As a result, in-depth studies conducted in relevant models are necessary to fully understand the natural history of NAFLD, and to identify sex-dependent determinants of NAFLD progression.…”
Section: [H1] Introductionmentioning
confidence: 99%
“…The fecal microbiota is a popular monitoring index requiring non-invasive sampling methods. In a mixed group, it is difficult to separate the main influencing factors, such as sex, distribution pattern, and environment [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study about Chinese forest musk deer showed no significant differences in the gut microbiota between males and females [ 25 ]. Several studies suggested that sexual dimorphism of the gut microbiota is associated with diseases, such as cardiovascular and cardiometabolic diseases [ 14 , 21 , 26 , 27 ]. Some other factors, including diet, age, sex hormones, and body mass index, influence the gut microbiota [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation